Zoledronate effects on systemic and jaw osteopenias in ovariectomized periostin-deficient mice. - Nicolas Bonnet (Public Library of Science (PLoS), 2013)
Osteoporosis and periodontal disease (PD) are frequently associated in the elderly, both concurring to the loss of jaw alveolar bone and finally of teeth. Bisphosphonates improve alveolar bone loss but have also been associated with osteonecrosis of the jaw (ONJ), particularly using oncological doses of zoledronate. The effects and therapeutic margin of zoledronate on jaw bone therefore remain uncertain. We reappraised the efficacy and safety of Zoledronate (Zol) in ovariectomized (OVX) periostin (Postn)-deficient mice, a unique genetic model of systemic and jaw osteopenia. Compared to vehicle, Zol 1M (100 µg/kg/month) and Zol 1W (100 µg/kg/week) for 3 months both significantly improved femur BMD, trabecular bone volume on tissue volume (BV/TV) and cortical bone volume in both OVX Postn(+/+) and Postn(-/-) (all p<0.01). Zol 1M and Zol 1W also improved jaw alveolar and basal BV/TV, although the highest dose (Zol 1W) was less efficient, particularly in Postn(-/-). Zol decreased osteoclast number and bone formation indices, i.e. MAR, MPm/BPm and BFR, independently in Postn(-/-) and Postn(+/+), both in the long bones and in deep jaw alveolar bone, without differences between Zol doses. Zol 1M and Zol 1W did not reactivate inflammation nor increase fibrous tissue in the bone marrow of the jaw, whereas the distance between the root and the enamel of the incisor (DRI) remained high in Postn(-/-) vs Postn(+/+) confirming latent inflammation and lack of crestal alveolar bone. Zol 1W and Zol 1M decreased osteocyte numbers in Postn(-/-) and Postn(+/+) mandible, and Zol 1W increased the number of empty lacunae in Postn(-/-), however no areas of necrotic bone were observed. These results demonstrate that zoledronate improves jaw osteopenia and suggest that in Postn(-/-) mice, zoledronate is not sufficient to induce bone necrosis.